A Sensitive Medium‐Throughput Method to Predict Intestinal Absorption in Humans Using Rat Intestinal Tissue Segments. Issue 9 (17th February 2015) - Da Silva, Laís Cristina; Da Silva, Taynara Lourenço; Antunes, Alisson Henrique; Rezende, Kênnia Rocha; Donovan, Maureen D.; Langguth, Peter; Polli, James E.; Tamai, Ikumi; Vig, Balvinder; Yu, Lawrence X.
<x xml:space="preserve">Abstract</x> A range of in vitro, ex vivo, and in vivo approaches are currently used for drug development. Highly predictive human intestinal absorption models remain lagging behind the times because of numerous variables concerning permeability through gastrointestinal tract in humans. However, there is a clear need for a drug permeability model early in the drug development process that can balance the requirements for high throughput and effective predictive potential. The present study developed a medium throughput screening Snapwell (MTS‐Snapwell) ex vivo model to provide an alternative method to classify drug permeability. Rat small intestine tissue segments were mounted in commercial Snapwell™ inserts. Unidirectional drug transport (A–B) was measured by collecting samples at different time points. Viability of intestinal tissue segments was measured by examining transepithelial electric resistance (TEER) and phenol red and caffeine transport. As a result, the apparent permeability (Papp; ×10−6 cm/s) was determined for atenolol (10.7 ± 1.2), caffeine (17.6 ± 3.1), cimetidine (6.9 ± 0.1), metoprolol (12.6 ± 0.7), theophylline (15.3 ± 1.6) and, ranitidine (3.8 ± 0.4). All drugs were classified in high/low permeability according to Biopharmaceutics Classification System showing high correlation with human data (r = 0.89). These findings showed a high correlation with human data (r = 0.89), suggesting that this model has potential predictive capacity for paracellular and transcellular passively absorbed molecules. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2807–2812, 2015